Phylogeography and demographic history of the Chagas disease vector Rhodnius nasutus (Hemiptera: Reduviidae) in the Brazilian Caatinga biome - Peretolchina, Tatiana; Pavan, Márcio G.; Corrêa-Antônio, Jessica; Gurgel-Gonçalves, Rodrigo; Lima, Marli M.; Monteiro, Fernando A. (PLOS Neglected Tropical Diseases, 2018)
Author summary Chagas disease is endemic to Latin America and the Caribbean and it is estimated that 6–7 million people are infected with the etiological agent Trypanosoma cruzi. Although new community-based ecosystem management (ecohealth) initiatives have been implemented, vector control based on insecticide-spraying of households remains one of the most effective strategies to diminish parasite transmission to humans. However, this strategy is not sustainable where native triatomine species are capable of colonizing peridomestic structures and invading human dwellings. The application of molecular markers with the potential of recovering both historical and contemporary information on vector population structure and diversity can improve the understanding of vector dissemination and thus contribute to the development of better disease control strategies. In this study we analyzed Rhodnius nasutus populations endemic to the Brazilian Caatinga biome using two sets of markers: a fragment of the mitochondrial gene cytochrome b and eight nuclear microsatellite loci. The information generated and described herein is important as it may contribute to the advancement of our understanding of Chagas disease vector ecology and phylogeography.